2021
DOI: 10.1007/s40843-020-1572-3
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur defect-rich WS2−x nanosheet electrocatalysts for N2 reduction

Abstract: Seeking catalysts with high electrocatalytic activity for ambient-condition N 2 reduction reaction (NRR) remains an ongoing challenge due to the chemical inertness of N 2. Herein, defect-rich WS 2 nanosheets (WS 2−x) were designed as an efficient electrocatalyst for NRR, which were prepared via vulcanizing the oxygen-vacancy-rich tungsten oxide in a vacuum tube. The sulfur defects were conducive to the adsorption and activation of N 2. In neutral electrolyte of 0.1 mol L −1 Na 2 SO 4 at −0.60 V vs. reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The NO adsorption configurations over both pristine and defective (with chalcogen vacancy) TMD surfaces and the corresponding adsorption energies are shown in Figure S1 and Table S1 (see ESI), respectively. For all the five TMD monolayers, the reported most stable vacancies are chalcogen vacancy [22h–j,l,m,24,40] . The most stable NO adsorption at a vacancy site is always through the N end and is much stronger than on the perfect surface.…”
Section: Resultsmentioning
confidence: 93%
“…The NO adsorption configurations over both pristine and defective (with chalcogen vacancy) TMD surfaces and the corresponding adsorption energies are shown in Figure S1 and Table S1 (see ESI), respectively. For all the five TMD monolayers, the reported most stable vacancies are chalcogen vacancy [22h–j,l,m,24,40] . The most stable NO adsorption at a vacancy site is always through the N end and is much stronger than on the perfect surface.…”
Section: Resultsmentioning
confidence: 93%
“…This was determined by analyzing the CV curves within the range of ∼0.26–0.36 V vs RHE, as depicted in Figure d,e. Furthermore, the high C dl value of 31.75 mF cm –2 (Figure e) indicates that Fe SAC -N-C possesses a high ECSA, which is beneficial for the NRR process. To further investigate the origin of the observed NRR activity of the Fe SAC -N-C catalyst, its Nyquist plot (Figure f) unraveled a narrower capacitance arc at −0.1 V vs RHE than that of the C–N, verifying the rapid charge transfer, and thus the better catalytic efficacy. Notably, the Fe SAC -N-C electrocatalyst exhibited a higher angle for the linear curve in the low frequency region when compared to that of the C–N counterpart.…”
Section: Resultsmentioning
confidence: 92%
“…S16 in the ESM) After the stability test, Ni maintained its valence state. For the S 2p spectra, the peak at 163.5 eV is assigned to the S-Ni species, and the peaks at 169.0 eV were assigned to the oxidized S [62]. It is found that Ni 3 S 2 NWs have a large portion of oxidized S species, which may cause by the rich defects in the NWs.…”
Section: The Ethanol Upgrading Activities Of the Ni 3 S 2 Nwsmentioning
confidence: 97%
“…It is found that Ni 3 S 2 NWs have a large portion of oxidized S species, which may cause by the rich defects in the NWs. The defect sites are easier to be oxides and thus lead to higher ethanol upgrading activity [62,63].…”
Section: The Ethanol Upgrading Activities Of the Ni 3 S 2 Nwsmentioning
confidence: 99%